State and Corporate Management of Region$1 (Bs Development in the Conditions of the Digital Economys - Buchaev, Yakhya G.; Abdulmanapov, Salikhbek G.; Abdulkadyrov, Arsen S.; Khachaturyan, Arutyun A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2021)
This edited book presents scientific and practical recommendations for the successful state and corporate management of regional development under the conditions of the digital economy. These conditions have produced a number of changes. On the one hand, new aspects of regional economies, which require management, are emerging, above all, digital technologies that have to be understood by the population, employees in the labor market, and regional companies. On the other hand, new opportunities for improving practices in the state and corporate management of regional development on the basis of digital technologies are also emerging: e-government systems, digital marketing, online trade, (3z(Bsmart(3y (Bregions, etc. This book provides an overview of the leading digital technologies and demonstrates how they can be used to improve modern practices in the state and corporate management of regional development in the digital economy. The authors develop the conceptual foundations and put forward practical recommendations. In closing, the authors$1 (Bconclusions and recommendations are applied to the example of modern Russia, ensuring the practical relevance of the research. .s
Modern region on the way to the digital economy: challenges for public and corporate management -- The model of digital development of a modern region: new challenges for state and corporate management -- Factors of development of the region$1 (Bs labour market in the conditions of the digital economy and the tools of their management -- Scientific and methodological provision of region$1 (Bs competitiveness assessment in the conditions of the digital economy -- The methodology of indicative assessment of the effectiveness of managing region$1 (Bs development in the conditions of the digital economy -- Development of Russia$1 (Bs regions in the conditions of the digital economy: management, effectiveness and competitiveness -- Digital entrepreneurship as a new subject of a modern region$1 (Bs economy: state stimulation and market mechanisms of development -- The regional system of science and education as a source of digital personnel and breakthrough technologies for region$1 (Bs economy -- Infrastructure of the digital economy for region$1 (Bs AIC: creation, measuring and development -- Perspectives of development of the system of e-government in the region in the conditions of the digital economy -- Digital society in a modern region: issues of its formation and ways of solving them on the basis of the labour market management in the agrarian sector.s
Keywords: Economic theory; Management information systems; Management; Political economy; Entrepreneurship; Economic Theory/Quantitative Economics/Mathematical Methods; Business Information Systems; Management; International Political Economy; Entrepreneurship